Keterlibatan Masyarakat Sipil dalam Pelaksanaan Program Kampung Iklim (ProKlim) di Kampung Kayu Ara Permai Kecamatan Sungai Apit Kabupaten Siak - Indah Deartati Sihotang; Sulaiman Zuhdi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze civil society involvement in the implementation of ProKlim in Kayu Ara Permai Village, Sungai Apit District, Siak Regency. The study used a descriptive qualitative approach with purposively selected informants, including the village government, ProKlim managers, community leaders, and residents involved in the program. Data were collected through interviews, observation, and documentation, then analyzed interactively using the Miles and Huberman model based on Cohen and Uphoff's participation dimensions. The results showed that community participation in all stages of ProKlim varied in intensity. The strongest participation was found in the implementation and utilization stages of the results through mutual cooperation, reforestation, waste management, and mangrove conservation. Conversely, participation in decision-making and evaluation was still limited because these processes were dominated by the village government and program administrators. The participation quadrant analysis placed community involvement in the mobilization participation category, indicating high involvement in program implementation, but not yet accompanied by an equal role in planning and evaluation. These findings indicate that the success of ProKlim still depends on strengthening community participation mechanisms in decision-making and evaluation to achieve more sustainable empowerment.